Robot dynamics and control - Spong, Mark W.; Vidyasagar, Mathukumalli ([S.l.] : John Wiley and Sons (WIE), 1989)
This textbook has been designed to introduce students to robot kinematics and dynamics. It includes a treatment of robot control, information on linear transformations, dynamics, manipulator control, robust control, force control, use of feedback in nonlinear systems and adaptive control.